Kültürel Mirasın İzlerini Kent Müzelerinde Sürmek: Trabzon Müzeleri / Following the Traces of Cultural Heritage Through City Museums: Trabzon Museums - Kurak Açıcı, Funda; Konakoğlu, Zeynep Nilsun (Journal of History Culture and Art Research, 2018)
Abstract Cities have existed throughout the history as a combination and conflict of various cultures. The values of citizens are shaped by cultural accumulation that is created from the past to our times. Cultural elements cover a wide scope of fields from science in life to art. The history of the city helps the recognition of the city’s architecture, music, tradition, habits and culture and creates the identity of the city. All of these elements that form a city constitute the cultural heritage of the city. The best witnesses of cultural heritage are city museums which present cities as they are. City museums are one of archive sources that contain all the information that may be gathered about a city. Museums are significant structures that transfer the past to the future, witness all the times experienced by cities and symbolize cities. This study was form around who the structure and culture of a city is reflected by museums, which are the strongest protectors of the cultural heritage of a city. This is why this study discusses the province of Trabzon which has hosted several civilizations from the past to the present and protected its cultural heritage, as well as its city museums. Information and documents were collected in relation to the city museums in the province of Trabzon, and city museums were discussed with the method of field surveys. The city of Trabzon has been covered in the scope of the study with the city’s museums where it preserves its cultural heritage. The museum contributes to the development and strengthening of the social consciousness as well as the transfer of the city’s values, and the values we make us with great care. The purpose of the study is to reveal the extent to which city museums protect the cultural heritage of the city and transfer it to future generations. Öz Tarih boyunca kentler pek çok kültürün birleşimi ve çatışmasıyla ile var olmuştur. Kentlilerin sahip oldukları değerler geçmişten günümüze gelen kültürel birikimlerle şekillenir. Kültürel öğeler, yaşam içinde bilimden sanata pek çok alanı kapsamaktadır. Kentin tarihi, mimarisi, müziği, gelenek ve göreneği kenti ve kentin kültürünün tanınmasına yardımcı olur ve kentin kimliğini oluşturur. Kenti meydana getiren tüm bu öğeler, kentin kültürel mirasını temsil eder. Kültürel mirasın izlerinin en iyi tanıkları, onları olduğu gibi sunan kent müzeleridir. Kent müzeleri kente dair elde edilebilecek tüm bilgileri içinde barındıran kentin en önemli arşiv kaynaklarından biridir. Müzeler, kent için geçmişi geleceğe aktaran, kentin tüm zamanlarına tanıklık eden ve kenti simgeleyen önemli yapılardır. Bir kentin kültürel mirasının en güçlü koruyucuları olan müzelerin, kentin yapısını ve kültürünü nasıl yansıttığı bu çalışmanın ana kurgusunu oluşturmaktadır. Bu nedenle geçmişten günümüze birçok medeniyete ev sahipliği yapmış olan Trabzon kenti, kültürel mirasını koruduğu kent müzeleri ile çalışma kapsamında ele alınmıştır. Kent müzeleri şehrin değerlerinin gelecek kuşaklara aktarılmasının yanı sıra, toplum bilincinin gelişip güçlenmesine de katkıda bulunmaktadır. Trabzon kentindeki tüm müzeler bizi bir çatı altında toplayan; tarihimizi, kültürümüzü, gelenek ve göreneğimizi, kısacası bizi biz yapan değerleri büyük bir titizlikle korumaktadır. Çalışmada, literatür araştırması ile kentin müzeleri ile ilgili bilgiler ve belgeler toplanmış ve yerinde gözlem yoluyla da kent müzeleri irdelenmiştir.